Alice in wonderland: ladybird classics - Kincaid, Lucy; Guile, Gill Carroll, Lewis (Brimax Books Newmarket, 1997)
When Alice follows the white rabbit down a rabbit-hole, she finds herself in an amazing wonderland and on an adventure involving the strangest characters. She meets the vanishing Cheshire Cat, is invited to a never-ending tea party and plays a game of croquet with the Queen of Hearts